Children's HIV Status and the Acceptance Stage of Grief amongst HIV-Positive Women - Ristriyani, Rizka; Rachmawati, Imami N; Afiyanti, Yati (Makara Journal of Health Research, 2018)
Background: Women living with HIV (WLWH) commonly grieve but may pass through the grieving process until reaching the acceptance stage. We try to identify the relationship between children's HIV status and the acceptance stage of grief amongst WLWH. Method: This cross-sectional study utilised consecutive sampling of 235 HIV-positive women in Jakarta, Indonesia. The women were assessed with the Acceptance of Disease and Impairments Questionnaire (ADIQ). Results: Most of the respondents were housewives (65.5%), had been diagnosed over one year previously (74.5%), had an HIV-positive spouse (60.4%), had more than one child (51.5%) but none who were infected (73.6%) and assumed that their HIV status was caused by their spouse (50.2%). The respondents' median score of acceptance of their HIV status was relatively high (3 on a 1-4 scale). This showed a significant negative correlation between children's HIV status and the acceptance stage amongst HIV-positive women (p = 0.01). Conclusion: Mother-to-child HIV transmission may disrupt the mother's acceptance stage because of feelings of guilt and difficulty disclosing their status. Because the children's HIV status was correlated with the mother's acceptance stage, WLWH must comply with the Preventing Mother-to-Child Transmission of HIV (PMTCT) program during the perinatal period.